Efficacy of Mirabegron Add-on Therapy to Oxybutynin for BPH Patients with Persistent Urgency on Oxybutynin Alone (International Journal of Psychosocial Rehabilitation, 2020)
Aims: To compare the efficacy of mirabegron add-on therapy for persistent overactive bladder (OAB) symptoms despite oxybutynin monotherapy in men with irritative lower urinary tract symptoms suggestive of benign prostatic hyperplasia Methods: 50 patients with persistent irritative lower urinary tract symptoms despite Ditropan monotherapy were randomized to receive add-on therapy with mirabegron (50 mg/day) for 3 months. Improvement in IPSS score and QOL were assessed in patients before and after addition of mirabegron at 3 months Result: From September 2018 to December 2019, 50 patients were enrolled in this study. 38 out of 50 patients got improvement in quality of life (QOL) score. The IPSS score had a mean improvement from 16.6 before the addition of mirabegron to 12.68 after 12 weeks of mirabegron addition. Conclusions: In our study, we noticed that the add-on mirabegron for patients already on anticholinergic drugs but still with persistent irritative LUTS had a good impact on IPSS score and QOL.